Technology‐enabled collaborative care for youth with early psychosis: Results of a feasibility study to improve physical health behaviours. Issue 10 (1st February 2022) - Melamed, Osnat; Voineskos, Aristotle; Vojtila, Lenka; Ashfaq, Iqra; Veldhuizen, Scott; Dragonetti, Rosa; Carriere, Rebecca; LaChance, Laura; Kohut, Sara Ahola; Tulloch, Trisha; Argarwal, Sri Mahavir; Hahn, Margaret; et al.
Abstract: Aim: Psychotic disorders are associated with excess morbidity and premature mortality. Contributing factors include tobacco smoking, low physical activity, and poor nutrition. This study tested a Technology‐Enabled Collaborative Care model to improve health behaviours among youth with early psychosis. Methods: A feasibility study among youth (ages 16–29) with early psychosis in Ontario, Canada. Participants were randomized to either a health coach supervised by a virtual care team (high intensity, n  = 29), or self‐directed learning (low intensity, n  = 23) for 12 weeks. The primary outcome was participant engagement, defined as self‐perceived benefit of changing health behaviours. Secondary outcomes were measures of health behaviours and programme‐use metrics. Results: Engagement was higher for high intensity participants for physical activity (adjusted group difference in change at 24 weeks = 3.4, CI95% = 1.9–4.9, p  < .001) and nutrition (adjusted difference = 2.9, CI95% = 1.2–4.6, p  = .001). No change was observed in health behaviours. Sixty two percent of participants completed 6 or more of the 12 weekly remote individualized health coaching sessions. Nine (39%) low intensity and 12 (41%) high intensity participants completed the final follow‐up. Conclusions: Personalized health coaching for youth with psychosis is feasible and may have sustained benefits. However, retention with this population for 12 weeks is challenging.